Qualitative and Quantitative Changes in Total Lipid Concentration and Lipid Fractions in Liver Tissue of Periparturient German Holstein Dairy Cows of Two Age Groups - Theinert, Kirsten B.; Snedec, Teja; Pietsch, Fabian; Theile, Sabrina; Leonhardt, Anne-Sophie; Spilke, Joachim; Pichelmann, Stefan; Bannert, Erik; Reichelt, Kristin; Dobeleit, Gabriele; Fuhrmann, Herbert; Baumgartner, Walter; et al. (Frontiers in Veterinary Science, 2022)
Fatty liver syndrome (FLS) is a common disease in high-producing dairy cows. Studies in humans suggest that the different hepatic lipid fractions play a role in this context. In dairy cows, little is known about the composition of fat stored in the liver, its periparturient dynamics, and the effect of cows´ age. Therefore, our goal was to generate primary data in healthy cows to serve as reference values for future studies. Eight healthy German Holstein cows (2nd lactation, n=3; ≥3rd lactation, n=5) were examined 14 d antepartum and 7, 28, and 42 d postpartum. The examinations included clinical assessment, liver biopsy, blood sampling, and recording of milk yield. Total lipids (TL) in liver tissue were measured gravimetrically. The TL were separated into lipid fractions (triacylglycerol, TAG; phospholipids, PL; non-esterified fatty acids, NEFA; and cholesterol esters) using thin-layer chromatography, followed by gas chromatography for fatty acid determination. Concentrations of NEFA, ß-hydroxybutyrate, and cholesterol were analyzed in blood. Concentrations of TL, TAG, NEFA, and cholesterol esters in liver tissue and NEFA in blood increased in the periparturient period. The older cows had higher hepatic TL, TAG, and phospholipid concentrations, higher relative hepatic concentrations of TAG in TL, higher NEFA concentrations in blood, a greater decrease in body condition, and higher milk yields between d 9 and 40 than the younger cows. We proposed that due to higher milk yield, older cows mobilized and deposited more fat in the liver, and the increase in hepatic TAG concentration was longer-lasting than in younger cows. Higher levels of structural lipids (PL) in older cows could be explained by higher demand for storage of TAG and cholesterol esters in lipid droplets or for the export of TAG via very-low-density lipoproteins. Results show that hepatic fat storage is a reversible process and does not necessarily cause clinical disease. Nevertheless, older cows have a more sustained and greater increase in hepatic TAG concentration, which may explain their increased risk of FLS. The results are limited in their extrapolation due to the small sample size and thereby possible selection bias but present a valuable basis for future studies.